2014
DOI: 10.1186/1475-2875-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategic roles for behaviour change communication in a changing malaria landscape

Abstract: Strong evidence suggests that quality strategic behaviour change communication (BCC) can improve malaria prevention and treatment behaviours. As progress is made towards malaria elimination, BCC becomes an even more important tool. BCC can be used 1) to reach populations who remain at risk as transmission dynamics change (e.g. mobile populations), 2) to facilitate identification of people with asymptomatic infections and their compliance with treatment, 3) to inform communities of the optimal timing of malaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
280
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(301 citation statements)
references
References 32 publications
19
280
2
Order By: Relevance
“…Distance and safety are two barriers to malaria professionals and health managers being able to provide continuous or even timely onsite medical support. Many studies have found significant morbidity and mortality among expatriate populations owing to malaria [7, 8], and lower KAP levels for prevention and treatment of malaria among non-immune travellers and expatriate workers [14]. Previous studies on health education strategies for malaria prevention have proved to be effective in improving malaria prevention KAP and decreasing rates of malaria morbidity [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Distance and safety are two barriers to malaria professionals and health managers being able to provide continuous or even timely onsite medical support. Many studies have found significant morbidity and mortality among expatriate populations owing to malaria [7, 8], and lower KAP levels for prevention and treatment of malaria among non-immune travellers and expatriate workers [14]. Previous studies on health education strategies for malaria prevention have proved to be effective in improving malaria prevention KAP and decreasing rates of malaria morbidity [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…[4951] These models also investigated the impact of various malaria interventions, the effect of cross border migration (between Mozambique and South Africa) on the persistence of malaria in South Africa and prospects of elimination.…”
Section: Mathematical Modelling Of Malaria Transmission Dynamicsmentioning
confidence: 99%
“…Impressive stories from Brazil and Egypt following its impactful malaria eradication motivates its revival [10] with current operation in Kenya [11], The Gambia [8], Burkina Faso, Benin [12] and Tanzania [13]. Low immobility, confinement to shallow water bodies, susceptibility to chemical attacks and less chances of developing resistance favor this vector control approach [14, 15].…”
Section: Introductionmentioning
confidence: 99%